EMBROIDERED BISHOI SHAWLS OF RAJASTHAN: THREADS OF ITS HISTORY - Patel, Falguni; Sharma, Kriti (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Rajasthan, the north-western state of India presents a great variety of tangible and intangible cultural heritage. Owing to its unique geographical position in the country, the place is full of historic influences and wealth of art with reflection of cultural diversity along with considerable amount of overlaps in practicing rituals and mode of dressing. The state features a number of embroideries with unique traditions in terms of their costumes and textiles. Amongst the different articles of adornment, the shawls of Bishnoi community of Rajasthan include varieties of tie and dye shawls or embroidered shawls or a combination of both. Growing globalization in the present day and time poses a considerable threat to the survival of traditional craft forms and hence the craft holds no past records regarding the origin of these Bishnoi shawls. Therefore, the objective of the study was to undertake a scientific exploration, of the heritage craft of these shawls which to trace and record the history and origin of the Bishnoi community embroidered shawls. The research under this paper takes an exploratory and descriptive method, both primary and secondary data were collected. Purposive sampling was adopted to visit antique collectors and museums and snowballing technique was used to advance the research further till primary Bishnoi respondents. The study unveiled the opulent and alluring history behind the embroidered shawl which sustains the cultural history of the region in their style of motifs with distinct embroidery motifs illustrating the influence of embroidery from Central Asia.